Model Pembelajaran Problem Based Learning Terhadap Kemampuan Menulis Teks Prosedur - Ariska Putri; Susy Deliani; Andi Syahputra Hrp; Siti Fatimah Zahara (Multiverse: Open Multidisciplinary Journal, 2022)
This study examines the problem-based learning model on the ability to write procedural texts in class XI students of SMA Al-Maksum Cinta Rakyat. The method used is an experimental method with a research design that is one group pretest-post test design. The population in this study were all students at totaling 128 students consisting of 67 male students and 61 female students. The sampling technique in this study is the random sampling technique, namely the technique of taking random samples with equal opportunities for all members of the population, so the sample in this study was class XI students at SMA Al-Maksum Cinta Rakyat. The average score of students who use the problem based learning (PBL) learning model is higher than the average value of students who use the lecture method, which is 81.2 compared to 67.26. Based on the results of the t-test calculation, it is obtained that tcount > t table or 33.54 > 1.692 then Ho is rejected. Thus it can be concluded that in using the PBL learning model there is an influence in the applied learning.